Rekonstruksi Makna Perceraian Perspektif Masyarakat Muslim di Kabupaten Malang - Dakwatul Chairah (Islamica: Jurnal Studi Keislaman, 2016)
This article explores the reconstruction of divorce in the understanding of Muslim community in Malang. Marriage in Islam is not only a civil bond, but also as a religious attachment that contains the values of worship. However, many Muslims fail to defend their marriage. Divorce at Religious Court of Malang district is recorded as very high in East Java. The divorce rate in the region of South Malang is the highest, with labor women as the majority population. They looked at divorce as the only way out to end the marriage. Divorce begins with conflicts, disputes and quarrels which negate the hope to live in harmony again in the household. The solution is understood by most of them as a normal thing that does not need to worry. These perceptions arise because of their lack of knowledge about the meaning of marriage and the danger of divorce with all its consequences. Infact, divorce can result in consequences which disturb the emotion of women and their social and economic conditions as the single parent.